Effect of a methyl-hydrazine derivative on the cellular respiration (Revista Española de Fisiología, 1969)
Effect of a Methyl-hydrazine Derived on Cellular RespirationThe effect of methyl 2-p-(isopropyl- carbamyl) Benzyl-hidrazine chlorhydrate on the respiration of yeast cells, rat diaphragm and liver homogenate has been studied. It was found that this drug does not produce appreciable alterations in O, consumption, the only observed effect being a discreet but significative drop in the exogenous respiration of the yeast with glucose.